Salivary duct carcinoma of the parotid gland: A case report and review of the literature - XIE, SHULE (Oncol Lett, 2015)
Salivary duct carcinoma (SDC) is a rare and aggressive parotid malignancy that most commonly affects males in the fifth and sixth decades of life. Histopathology specimens obtained from SDC patients demonstrate a resemblance to ductal carcinoma of the breast. Therefore, to distinguish SDC from breast ductal carcinoma, several immunohistochemical markers exist that may enable surgeons to make an accurate diagnosis. In this study, the case of a 54-year-old male with salivary duct carcinoma of the right parotid gland is presented. The results of the present case study revealed that the SDC sample was positive for the expression of human epidermal growth factor 2 (Her-2), cytokeratin (CK) 8/CK 18, p63, high molecular weight CK and calponin, and negative for expression of the estrogen receptor and progesterone receptor. Based on the result, an ipsilateral selective neck dissection followed by adjuvant post-operative radiation therapy was suitable at the primary treatment stage. At one year of follow-up, the patient was alive and free of recurrence. In advanced cases of SDC, treatment with anti-HER-2 monoclonal antibodies, such as trastuzumab, is recommended.